SAFETY RISKS AND MEASURES IN THE MAINTENANCE AND CLEANING OF SOLAR PANELS - D.B. Rakhimov (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
The growing global demand for energy has led to increased adoption of renewable energy technologies, especially solar power systems, due to their sustainability and environmental benefits. However, the operation and maintenance of solar panels—particularly cleaning processes—introduce a variety of safety risks. This article examines these risks in detail, focusing on mechanical hazards, electrical dangers, and environmental factors involved in maintaining rooftop and building-integrated photovoltaic (BIPV) systems. The paper highlights the importance of preventative maintenance, such as regular inspection for mechanical damage, electrical system checks, snow removal, and cleanliness of panels. Particular emphasis is placed on risks associated with working at heights, including falls, improper use of tools, and weather-related hazards such as slippery surfaces or high UV exposure. Furthermore, damage to equipment during cleaning or servicing is a critical concern that can reduce panel efficiency or lead to complete system failure. The study presents mitigation strategies, including personal protective equipment (PPE), system shutdown procedures, and specialized safety training. It advocates for integration of safety practices into standard building codes and emphasizes the necessity of updating regulations, such as SNIP 2.01.07-1996, to reflect current technologies. The paper concludes that systematic training, proper equipment handling, adherence to safety protocols, and regular maintenance scheduling are essential for reducing occupational hazards and prolonging the lifespan and performance of solar systems.